2019
DOI: 10.1042/bsr20180765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transplantation of FGF-2-transfected MSCs and XACB on TNF-α expression with avascular necrosis of the femoral head in rabbits

Abstract: Objective: The present study aimed to investigate the effect of the transplantation of basic fibroblast growth factor (FGF-2) gene-transfected mesenchymal stem cells (MSCs) and xenogeneic antigen-cancellous bone (XACB) on tumor necrosis factor-α (TNF-α) expression with avascular necrosis of the femoral head (ANFH) in rabbits. Methods: The models of steroid-induced osteonecrosis in rabbits were randomly divided into five groups: A (model), B (XACB), C (XACB + MSCs), D (XACB + MSCs + LV), and E (XACB + MSCs + LV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…As a result, there has been an increased focus on early interventions for AVN, aimed at preservation of the native articulation [4]. Core decompression (CD) is currently the most widely accepted treatment for early-stage AVN of the FH; however, due to limited efficacy, its use has been debated [5].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there has been an increased focus on early interventions for AVN, aimed at preservation of the native articulation [4]. Core decompression (CD) is currently the most widely accepted treatment for early-stage AVN of the FH; however, due to limited efficacy, its use has been debated [5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it inhibits osteogenic differentiation, thereby destroying bone tissue ( Osta et al, 2014 ). Peng et al (2018) and Peng et al (2019) combined FGF-transfected BMSCs with xenogeneic antigens of cancellous bone (XACB) to generate tissue-engineered bone (XACB/FGF/BMSCs) and implanted these BMSCs into the necrotic region of rabbits with early ONFH after CD. After 3, 6, and 12 weeks of implantation, the expression of OPG and RANKL was significantly increased in the femoral head.…”
Section: Therapeutic Applications Of Growth Factors For Osteonecrosis...mentioning
confidence: 99%
“…It was demonstrated in a rabbit model that FGF-2-transfected MSCs in a xenogeneic antigen-cancellous bone (XACB) scaffold can improve bone regeneration. It was found that TNF-α expression was inhibited by increased FGF-2 expression, which might have triggered the improved bone regeneration response in the steroid-induced osteonecrosis rabbit model [ 98 ]. Another study used bone MSCs transfected with both VEGF and BMP-6 in conjugation with a poly lactide-co-glycolide (PLAGA) hydrogel that were implanted subcutaneously in nude mice.…”
Section: Tissue Engineering/regenerative Therapiesmentioning
confidence: 99%